2010
DOI: 10.1590/s1980-65232010000100017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of topical acidulated phosphate fluoride on surface roughness of human enamel and different restorative materials

Abstract: Purpose: The aim of this study was to assess the influence of topical acidulated phosphate fluoride on the surface roughness of both human enamel and different restorative materials.Methods: Resin-modified glass ionomer (Vitremer -V), microhybrid composite resin with fluoride (Tetric Ceram -T), and nanofiller composite resin without fluoride (Z350 -Z) were evaluated. Acidulated phosphate fluoride (APF, 1.23%) was applied to half of the specimens (groups VF, TF, ZF and EF). Ten intact human third molars were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
9
1
1
Order By: Relevance
“…Papagiannoulis et al [67] stated that fluoride can disrupt the filler-matrix interface through three possible mechanisms: (1) hydrogen bonds of silanol groups are affected by rearrangement of the water monolayer adsorbed on filler, (2) hydrolysis of the organosilicon ester group, and (3) disorganization of the siloxane network formed from the condensation of intramolecular silanol groups, which stabilizes the interface. However, our findings are contrary to that of Botta et al [66], who found that the topical application of APF did not cause alteration in surface roughness of FZ350. Such contrary could be related to the difference in the type and concentration of fluoride agents used.…”
Section: Different Superscript Numbers In the Same Column Indicating contrasting
confidence: 99%
See 2 more Smart Citations
“…Papagiannoulis et al [67] stated that fluoride can disrupt the filler-matrix interface through three possible mechanisms: (1) hydrogen bonds of silanol groups are affected by rearrangement of the water monolayer adsorbed on filler, (2) hydrolysis of the organosilicon ester group, and (3) disorganization of the siloxane network formed from the condensation of intramolecular silanol groups, which stabilizes the interface. However, our findings are contrary to that of Botta et al [66], who found that the topical application of APF did not cause alteration in surface roughness of FZ350. Such contrary could be related to the difference in the type and concentration of fluoride agents used.…”
Section: Different Superscript Numbers In the Same Column Indicating contrasting
confidence: 99%
“…Phosphoric acid has the ability to etch the filler particles [14] , that exposed after degradation of the superficial resin matrix due to water sorption and when these fillers are very small, as in the nanocomposite, the size of the defects left are practically undetectable, resulting in surface smoothening [65] . Another possible cause for a such smoothening effect could be attributed to the retention of CPP-ACP nano-clusters in the porosities created by water sorption [66] . On the other hand, the high roughness values of VF after application of TMP may be related to the large filler particles size of this microhybride composite in comparison to that of nano-composites.…”
Section: Different Superscript Numbers In the Same Column Indicating mentioning
confidence: 99%
See 1 more Smart Citation
“…It means that the starting point of surface roughness value was above critical value for bacterial colonization (0.2 µm). 21 The study suggested that the application of CPP-ACP containing fluoride before and after bleaching was effective in reducing S. mutans accumulation and enamel roughness.…”
Section: Discussionmentioning
confidence: 98%
“…Um cálculo amostral foi realizado no site "openepi.com" para comparação de médias. Para tal, foram utilizados os seguintes parâmetros: intervalo de confiança bilateral de 95%, poder do estudo de 80%, e diferença média de 4,2 Ra (μm) entre grupos, valor baseado em um estudo anterior 14 . O resultado foi um tamanho amostral de n = 15 espécimes por grupo necessárias para encontrar diferença estatística na média de rugosidade superficial.…”
Section: Preparo Dos Espécimesunclassified